2023
DOI: 10.3390/biomimetics8010058
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of the Sustainability of Alkali-Activated Binders

Abstract: Limiting the consumption of nonrenewable resources and minimizing waste production and associated gas emissions are the main priority of the construction sector to achieve a sustainable future. This study investigates the sustainability performance of newly developed binders known as alkali-activated binders (AABs). These AABs work satisfactorily in creating and enhancing the concept of greenhouse construction in accordance with sustainability standards. These novel binders are founded on the notion of utilizi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…With regards to availability/ease of use, for architects and engineers, using a material that is readily available and easy to work with can save time and money on a project. This aligns with prior research demonstrating that resource availability has a direct impact on construction project costs and timelines (Alhassan et al, 2023;Habert et al, 2020). Furthermore, it has been observed that when resources are readily available, it facilitates efficient construction processes and reduces the need to extensively search for alternative materials or methods.…”
Section: Architectssupporting
confidence: 85%
“…With regards to availability/ease of use, for architects and engineers, using a material that is readily available and easy to work with can save time and money on a project. This aligns with prior research demonstrating that resource availability has a direct impact on construction project costs and timelines (Alhassan et al, 2023;Habert et al, 2020). Furthermore, it has been observed that when resources are readily available, it facilitates efficient construction processes and reduces the need to extensively search for alternative materials or methods.…”
Section: Architectssupporting
confidence: 85%
“…Hence, FA often requires the use of higher activation temperatures, to the order of 60-90 • C. In addition, activation with strong hydroxides or a mixture of silicates and hydroxides often occurs. Otherwise, the compressive strengths obtained are very low, making the structural use of AAMs impossible [46,47]. Zeolites undergo polymerization even more difficult than that of FA; for example, in the work of Nikolov et al, zeolites were activated with sodium silicate, sodium hydroxide, and sodium carbonate, and it was shown that the best parameters were obtained for activation with pure sodium silicate; nevertheless, the obtained compressive strengths were only a few MPa [42].…”
Section: Discussionmentioning
confidence: 99%
“…Strength and durability can be improved using nanomaterials in conjunction with modified cement binders [182]. Therefore, a significant reduction in service and maintenance costs is expected [183].…”
Section: Nanotechnologymentioning
confidence: 99%